Objective-C pocket reference - Duncan, Andy (O'Reilly, 2002)
Objective-C is an exciting and dynamic approach to C-based object-oriented programming; it's the approach adopted by Apple as the foundation for programming under Mac OS X, a Unix-based operating system gaining wide acceptance among programmers and other technologists. Objective-C is easy to learn and has a simple elegance that is a welcome breath of fresh air after the abstruse and confusing C++. To help you master the fundamentals of this language, you'll want to keep the Objective-C Pocket Reference close at hand. This small book contains a wealth of valuable information to speed you ove.